MY-T study: Symptom-based titration decisions when using testosterone nasal gel, Natesto® - Lee, Jay; Brock, Gerald; Barkin, Jack; Bryson, Nathan; Gronski, Matthew A.; Ormsby, Ross (Canadian Urological Association Journal, 2019)
Introduction: Natesto®, testosterone nasal gel (TNG), is a testosterone therapy (TTh) indicated for adult male hypogonadism.1 This study allowed titration decisions to be based on physicians’ assessment of patient symptoms. Methods: Hypogonadal males on active topical testosterone therapy (TThE) or naive to any form of testosterone therapy (TThN) were treated with 22 mg TNG daily (11 mg twice daily) for 90 days. Titration was determined by the physician at day 90 wherein the dose was increased to 33 mg daily if symptoms were not properly managed. Total testosterone (TT) levels were collected at day 90 and 120 and the quantitative Androgen Deficiency in the Aging Male (qADAM) symptom questionnaire was administered on days 0, 30, 60, 90, and 120. Results: At study endpoint, 77.0% of all patients were in the normal TT range. Mean qADAM scores increased from 30.8 at baseline to 35.5 (6.6) at day 90. Physician assessments resulted in 37% patients being up-titrated for an additional 30 days, however, qADAM scores did not change significantly at the higher dose. Conclusions: The majority of patients achieved the normal range of testosterone with TNG when physicians based their titration decision on an assessment of symptoms. Sexual function and energyrelated symptoms were predictive of improvements resulting from treatment. These symptoms were the most relevant indicators for physicians in making decisions relating to titration.